Insights Into Canada’s Digital Media, Branding and Political Image Management - Bohatyrets, Valentyna (Chernivtsi National University, 2021)
Owing to the different architectures of social media platforms as well as information revolution and globalization, digital media, branding and political image management prove to have become of significant value in changing the landscape and essence of traditional political campaigning into one of the most proficient and sophisticated marketing tactics. The study delves into the academic underpinnings of digital (virtual) or e-diplomacy that significantly contributes to the embracing of a nation branding and its manifold implications for any statehood. In the 21st Century, a new institution is emerging with some characteristics similar to the Fourth Estate, but with sufficiently distinctive and important features to warrant its recognition as a new Fifth Estate. Such ‘networks of networks’ enable the networked individuals to move across, undermine and go beyond the boundaries of existing institutions, thereby opening new ways of increasing the accountability of politicians, press, experts and other loci of power and influence. When theorizing on the topics of digital media, branding and political image management, the conclusive arguments indicate that social media indeed pose campaign environments distinct from mass communication arenas. Demonstrating beneficial personality traits and improving name recognition is a campaign to internalize a whole set of platform-specific affordances on social media in order to demonstrate that it represents the ‘state of the art’. This is a valuable insight and it is an important step forward in our understanding of a political image. A concluding remark is a political leader’s or a country’s image-making is a very multidimensional process, which involves different political, economic, social, cultural and communication aspects of a country’s development.
Роль цифрових медіа Канади у створенні національного брендингу та формуванні іміджу політика
Keywords: digiplomacy; political image; Canada; networks; digital media; branding; social media; politics; image making